2012
DOI: 10.1109/tps.2012.2193621
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effect of Corona Discharges in Atmospheric Air

Abstract: This paper explores the possibilities of using impulsive and steady-state corona discharges for biodecontamination operations. A high tension tubular corona electrode was stressed with positive or negative dc voltage with magnitude up to 26 kV, and a grounded mesh was used as an opposite electrode. Different operational regimes of this corona generator were investigated for the production of ozone in air flow and the inactivation of microorganisms. The test microorganisms used in this work were Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…This difference is even more marked in the case of the HV electrode with the largest tip radius (0.8 mm), where the standard deviation for positive breakdown voltage was an order of magnitude higher than for negative polarity, ±5 kV and ±0.5 kV, respectively. Potentially this effect (higher deviation in positive spark breakdown voltages) can be a result of different mechanisms of initiation and development of positive and negative corona discharges in air: in the case of increasing of HV stress, the development of positive corona discharges progresses through different stages including a highly unstable and volatile impulsive (flashing) corona stage, while the behaviour of the negative corona discharges is more predictable, typically negative corona current is a combination of DC component and Trichel impulses, [21].…”
Section: Resultsmentioning
confidence: 99%
“…This difference is even more marked in the case of the HV electrode with the largest tip radius (0.8 mm), where the standard deviation for positive breakdown voltage was an order of magnitude higher than for negative polarity, ±5 kV and ±0.5 kV, respectively. Potentially this effect (higher deviation in positive spark breakdown voltages) can be a result of different mechanisms of initiation and development of positive and negative corona discharges in air: in the case of increasing of HV stress, the development of positive corona discharges progresses through different stages including a highly unstable and volatile impulsive (flashing) corona stage, while the behaviour of the negative corona discharges is more predictable, typically negative corona current is a combination of DC component and Trichel impulses, [21].…”
Section: Resultsmentioning
confidence: 99%
“…The predominant reactive species in corona plasma was reported to be ozone (Gaunt et al 2006). Positive steady-state corona discharges in air normally generate less ozone as compared with negative corona at the same energization potential (Timoshkin et al 2012). The energy of the reactive species can be transferred effectively to other molecules through inelastic collisions (Zou et al 2006).…”
Section: Inactivation Of Inoculated Foodborne Pathogensmentioning
confidence: 99%
“…Even the initial expenses and operating costs are lower compared to other kinds of discharges, which generally require complex systems (Scholtz et al 2010). The chemical composition of plasma generated by atmospheric pressure corona discharges in air is complex and not fully understood (Timoshkin et al 2012). These discharges are known to produce chemically active species: oxygen ions and other charged species such as N + , NO + , NO − , hydroxyl and hydroperoxyl radicals (OH and HO 2 ), hydrogen peroxide (H 2 O 2 ), nitrous oxide (N 2 O) and other nitrogen oxide species (NO,NO 2 ,N 2 O 4 and N 2 O 5 ), and neutral species in their ground and excited states, including atomic oxygen, ozone and oxygen molecules in the singlet state (Pontiga et al 2002;Joshi et al 2011), which act as very strong oxidizers (Deng et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in the case of non-thermal atmospheric air plasmas, or plasmas in which oxygen is used as a component of the gaseous environment, reactive oxygen species may have a dominant effect in the inactivation processes. For example, a correlation between ozone generation and the bactericidal efficacy of atmospheric corona discharges is discussed in [6]. Ozone was used as an indicator of the generation of reactive oxygen species, and the role of each individual species was not determined.…”
Section: Introductionmentioning
confidence: 99%